Functional feed for Atlantic salmon (Salmo salar L.). Effect on gastrointestinal tract during parr-smolt transformation and susceptibility to infectious pancreatic necrosis virus (IPNV) - Johansson, Gunhild Seljehaug (UiT The Arctic University of Norway, 2014)
Atlantic salmon (Salmo salar L.) aquaculture is a relatively new industry in Norway, dating back to the 1960s. It has since then developed in to a profitable industry. Continuous improvement of hygiene control, knowledge of fish nutrition and health has been important for this development. Fish nutrition is a research field that has been increasingly focused on partly due to more use of plant raw materials as substitute for the less sustainable marine sources. The search for feed components meeting the nutritional requirements, improving fish health, growth and disease resistance is continuous. Feed producers produce functional feed by implementing functional ingredients that have positive effect on the fish. In this study, Atlantic salmon were fed a control diet and two different functional feeds during the parr-smolt transformation in freshwater and subsequently in seawater. The feed effects on the salmon gastrointestinal (GI) tract were investigated using light microscopy combined with a qualitative histological scoring system and real time polymerase chain reaction (PCR). Results from the histological analyses showed that feeding salmon with functional feeds produces less morphological changes to the GI tract compared to the control diet. The relative expression of pro- and anti-inflammatory genes was low during both periods. A mortality test using an Infectious pancreatic necrosis virus (IPNV) cohabitant challenge model revealed a significantly lower susceptibility and mortality in fish fed the functional diet. Numerous morphological observations were done during the histological examination from the feed- and challenge trial. Furthermore IPNV were detected by immunolabeling and transmission electron microscopy in pyloric caeca and distal intestine enterocytes. The results of this study showed that salmon fed a diet containing added vitamins, prebiotics, nucleotides and beta-glucans during the parr-smolt transformation period had significantly better gut status than the control diet two weeks post seawater ...